Stock market analysis as a financing alternative for SMEs in Latin America - Céspedes López, Jairo Beymar (2019)
In Latin America, Small and Medium Enterprises (SMEs) are in constant growth, and to finance it they require resources from third parties, the traditional way of doing it is through banking, however, there is another attractive alternative in the system, which it is the stock market, in its sector of both variable income and fixed income, and the alternative stock markets existing in the region. This article analyzes the Latin American situation of SMEs and their stock markets, their perception of financing, their benefits and reasons for doing, or not using this strategic alternative. This analysis is made based on real market data and assuming a critical and proactive position of the alternative to business financing in the region.